A cross sectional study on prevalence of hypertension and its associated risk factors among rural adults in Kanchipuram district, Tamil Nadu - Raja, T. K.; Muthukumar, T.; Mohan P., Anisha (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is one of the non-communicable diseases, which is an important global public health problem and also the most leading cause for cardiovascular disease in both developed and developing countries. The aim and objectives of the study were to estimate the prevalence of hypertension and to assess the associated risk factors among adults of rural population. Methods: A community based cross sectional study was done on 225 study subjects, using systemic random sampling method at Kancheepuram district, Tamil Nadu. Results: The study included 225 participants of which 53% were male and 47% were female. The overall prevalence of hypertension among the study population was 26.2%. Risk among male was greater than female (OR=1.390). Factors like age, body mass index, diet, family history of hypertension had significant association (p<0.05) with hypertension. Conclusions: Regular screening for hypertension among adults should be done in the general OPD as well as in health camps so that they have a knowledge regarding their own blood pressure status. Among those who already have hypertension, anti -hypertensive drugs, timely blood pressure check-up, screening for cardio vascular diseases and self-care management of hypertension need to be promoted.